Report of the Review Committee on Legal Education in the Caribbean 1996 (CLE TT)
Aims to investigate the systems of costs allocation and quota in order to establish the appropriate criteria for determining the optimum capacity for each Law School to accommodate students wishing to undergo training for the Legal Education Certificate.
Keywords: LEGAL SCIENCES